Investigations of Spectroscopic Factors and Sum Rules from the Single Neutron Transfer Reaction 111Cd(d→$\overrightarrow {\rm{d}} $,p)112Cd - Jamieson D.S. (EPJ Web of Conferences, 2014)
Cadmium isotopes have been presented for decades as excellent examples of vibrational nuclei, with low-lying levels interpreted as multi-phonon quadrupole, octupole, and mixed-symmetry states. A large amount of spectroscopic data has been obtained through various experimental studies of cadmiumisotopes. In the present work, the 111Cd(d→$\overrightarrow {\rm{d}} $,p)112Cd reaction was used to investigate the single-particle structure of the 112Cd nucleus. A 22 MeV beam of polarized deuterons was obtained at the Maier-Leibnitz laboratory in Garching, Germany. The reaction ejectiles were momentum analyzed using a Q3D spectrograph, and 130 levels have been identified up to 4.2 MeV of excitation energy. Using DWBA analysis with optical model calculations, spin-parity assignments have been made for observed levels, and spectroscopic factors have been extracted from the experimental angular distributions of differential cross section and analyzing power. In this high energy resolution investigation, many additional levels have been observed compared with the previous (d,p) study using 8 MeV deuterons [1]. There were a total of 44 new levels observed, and the parity assignments of 34 levels were improved.